Exploring Chemistry with Pyridine Derivatives - Pal, Satyanarayan (IntechOpen, 2023)
This book discusses the chemistry and applications of pyridine derivatives. The library of pyridine derivatives is growing steadily with numerous synthetic analogues already described and the identification of new, naturally occurring pyridine-based compounds. The book includes ten chapters organized into two parts. The first part focuses on the numerous types of reactions that arise from pyridine derivatives. The second part examines the pharmaceutical applications of pyridine derivatives as well as their usefulness as sensors for metal cations and extracting agents for platinum group metals.